Phygital workspace: a systematic review in developing a new typological work environment using XR technology to reduce the carbon footprint - Lo, Tian Tian Sky; Chen, Yuting; Lai, Tim Yu; Goodman, Andrew (Frontiers in Built Environment, 2024)
The urgency of environmental sustainability has catalyzed a thorough reconsideration of traditional workspaces and their environmental impact, particularly concerning carbon footprint stemming from business-related travel and daily commutes. In response to these concerns, the innovative notion of the "Phygital Workspace" has arisen. Moreover, the advent of the COVID-19 pandemic has accelerated the proliferation of this technology.In a Phygital Workspace, physical and digital elements coexist and interact to enhance productivity, collaboration, and overall work experience. This integration is often facilitated using advanced digital technologies, such as Augmented Reality (AR), Virtual Reality (VR), Mixed Reality (MR), and other immersive or interactive tools. This conceptual framework sets the stage for the seamless integration of both physical and digital dimensions, empowered by the potential of Extended Reality (XR) technology. An integral part of this review involves the analysis of various workspace scenarios, and further examines the role of a Phygital Workspace plays in reducing carbon footprint within each context. The scenarios under examination include flexible workspace scenarios, field work scenarios, and hybrid work scenarios. XR technology's contributions to reducing carbon footprint are evaluated by minimizing the need for physical travel, enabling remote collaboration, and enhancing workspace efficiency within these scenarios.Employing a systematic review methodology, this review considers the status of XR technology adoption in diverse business environments, pinpointing its strengths and limitations. The aim is to provide a solid foundation for the framework of a new typological work environment that leverages XR technology to effectively reduce the carbon footprint associated with travel. The framework comprises four key dimensions: XR Infrastructure, Collaborative Work Environment, Social Interaction Enhancement, and Environmental Impact Assessment. These dimensions collectively guide the development and implementation of sustainable Phygital Workspaces, catering to technological, social, and ecological considerations. It is an impassioned call for collaborative efforts among researchers, policymakers, and organizations to converge their expertise for a more environmentally conscious future of work.